PEMIKIRAN JABARIAH, QADARIAH DAN ASY’ARIAH - Husyin Saputra; Muhammad Amri; Indo Santalia (CV. Adiba Aisha Amira, 2022)
This journal covers significant debates on the topic of human activities (af'al ai-'ibad). The study examines human strength (istitha'ah) and will (masyi'ah). This is so because every deed is motivated by power and will. The issue is whether or not humans are free to choose their actions based on their own will and strength, or if all human choices are predetermined by God's qadha and qadhar. The Qadariyah understanding, Jabariyah understanding, and Asy'ariah understanding were then born out of this difficulty. Islam's development of the Qadariyah thinking was impacted by the free understanding that emerged among Christians. According to Jabaryah, Allah swt has predetermined every event that people have, both past and present, including bad luck and calamity. People lack free will and free choice, like water flowing in many ways. Just Allah (swt). In accordance with Asy'ariah, since God is free and without restrictions and has the nature of jaiz, humans do not possess freedom